The Importance of Ecological Redundancy for Ecosystems Restoration - Londe, Vinícius (Research in Ecology, 2021)
Restoration ecology is a multidisciplinary science that exchanges several concepts with other scientific fields to improve its practices. In this article, I discuss the ecological redundancy concept and its implications and applications on ecological restoration. Ecological redundancy was coined in the early 1990s to characterize those species that play similar (equivalent) functions in the ecosystem. The concept made it possible to segregate species into functional groups that operate in maintaining the system. I searched the literature and found that although some restoration models naturally consider this concept, studies in areas undergoing restoration which directly measure and test the ecological redundancy are still rare (n = 14). I provide evidence that distinguishing redundant species and identifying key species is feasible for ecological restoration. Additionally, I suggest that redundancy should also be part of the restoration monitoring, for example, by checking if functional groups have been recovered. Theory predicts that if ecological redundancy is correctly incorporated in restoration, projects with more chances of success will be created because redundancy tends to increase ecosystem resilience. Resilience is a crucial factor for restoration sustainability in a changing environment.